Technical vault: Front handspring - Watanabe, M. (Technique, 1997)
The handspring vault is used as the technical vault in the USA Gymnastics J.O. Compulsory program for all levels. This basic vault does not require complex technique in its performance, but through mastery of the basics, gymnasts will develop and refine essential techniques that will serve them well when learning other more complex vaults. The main components of vaulting (such as running form and speed, hurdle step onto the board, quick and powerful take-off from the board, turn over from the board to the horse and repulsion off the horse) can all be refined and developed by learning a technically good handspring vault. One of the important and critical technical aspects of the front handspring is the ability to utilize the power of full running speed and body rotation at the take-off without the concern of over rotation. If the gymnast slows down his running speed to control his body rotation in the post-flight, it defeats the purpose of this technical vault. The main focus of this article is to discuss the techniques coaches should look for in order to permit the gymnast to control post-flight rotation.